Effect of low-dose tungsten on human thyroid stem/precursor cells and their progeny. Issue 8 (August 2019) - Gianì, Fiorenza; Pandini, Giuseppe; Scalisi, Nunzio Massimo; Vigneri, Paolo; Fazzari, Carmine; Malandrino, Pasqualino; Russo, Marco; Masucci, Romilda; Belfiore, Antonino; Pellegriti, Gwabriella; Vigneri, Riccardo
Abstract : Thyroid cancer incidence is increased in volcanic areas where environment pollution biocontaminates residents. Tungsten (W) is the most increased heavy metal in drinking water of Mount Etna volcanic area where it exceeds the normal range in the urine of 27% inhabitants. The possible connection between increased tungsten and thyroid cancer has never been studied. We investigated in vitro the effect tungsten on both human thyrocytes in primary culture, thyrospheres (aggregates of stem/precursor thyroid cells) and thyrocytes differentiated from tungsten-exposed thyrospheres. Chronic exposure to low-dose (nanomolar range, as in the urines of volcanic area residents) soluble tungsten had major biological effects on thyroid stem/precursor cells, promoting growth with a biphasic (hormetic) dose-response and reducing apoptosis. No such effects were observed in mature thyrocytes. In addition, tungsten-exposed thyrospheres had abnormal expression of genes commonly altered also in thyroid cancer and increased activation of the DNA-repair proteins H2AX and 53BP1. Moreover, exposure to tungsten decreased thyrosphere differentiation, as indicated by the reduced expression of thyroid-specific genes in derived thyrocytes that also showed preneoplastic changes such as increased anchorage-independent growth, clonogenic growth and migration capacity. The mechanism of action of tungsten on thyroid stem/precursor cells is unclear but involves membrane G-proteins and activation of the ERK signaling pathway. These data indicate that chronic exposure to slightly increased tungsten, harmless for mature thyrocytes, importantly affects the biology of stem/precursor thyroid cells and of their progeny, inducing characteristics of preneoplastic transformation.